1070 IMPACT OF ECONOMIC FACTORS, SOCIAL HEALTH AND RECENT STRESSORS ON PHYSICAL HEALTH-RELATED QUALITY OF LIFE TRAJECTORIES. (14th June 2022) - Phyo, A Z Z; Gonzalez-Chica, D; Stocks, N; Woods, R; Fisher, J; Tran, T; Owen, A; Ward, S; Britt, C; Ryan, J; Freak-Poli, R
Abstract: Introduction: Poorer physical health-related quality of life (HRQoL) has been shown to predict a higher risk of adverse health outcomes including cognitive decline, cardiovascular disease, and mortality among community-dwelling older individuals. However, little is known about how physical HRQoL changes over time in older people and the predictors of this trajectory. This study (a) identified trajectories of physical HRQoL among older people and (b) explored whether economic factors, social health, or recent stressors impact physical HRQoL trajectories. Method: A cohort of 12, 506 community-dwelling Australians aged ≥70 years (54.4% females), enrolled in the ASPREE Longitudinal Study of Older Persons (ALSOP) study and was followed for six years. Physical HRQoL was assessed by using a validated instrument (SF-12; version-2) at baseline and over up to six annual follow-ups. Economic factors, social health, and recent stressors (i.e. stressful life events in the last 12 months) were assessed through a questionnaire at baseline. Growth mixture and structural equation modelling were used to identify physical HRQoL trajectories and their predictors. Results: Four physical HRQoL trajectories were identified—stable low (7.1%), declining (9.0%), stable intermediate (17.9%) and stable high (66.0%). Living in more disadvantaged areas, having economic burden, no voluntary work, loneliness, or recent stressors (i.e. spousal illness, friend/family illness, financial problem, pet died) were associated with a 10%–152% higher likelihood of being in the stable low or declining physical HRQoL trajectory than the stable high group. Conclusion: Specific stressors including financial hardship had a greater impact on adverse physical HRQoL trajectories in older people than other factors. This study highlights that grassroots approaches are needed to emphasize economic autonomy and social support networks in order to support the wellbeing of older people. Volunteering may prevent physical HRQoL decline and requires further investigation.